A STUDY OF ADVANCE ORGANIZER MODEL AMONG HIGHER SECONDARY STUDENTS IN LEARNING PHYSICS - S. KARTHIKEYAN; S.P.DENISIA (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The world in which the students live now must confront the future in different ways and it will be more complex than the past. Because the world is changing and likewise the idea, aspiration and attitude of the people are also going on changing. Accordingly, the entire process of education will go on changing. If the process of education changes the teaching, procedures will be changed differently. Teaching is not just to sit on an armchair with a cup of tea in hand to sip. It is an art and skill to be learnt. It requires the knowledge of content, method, techniques and teaching aids to be used for making teaching interesting and effective. Teaching provides to bring desirable changes in the behaviour of the learner. For that purpose, only the teacher has to apply new teaching strategies in the classroom.